Implementasi Project-Based Learning Berbasis Lingkungan Sekitar Untuk Meningkatkan Kesadaran Geosains Siswa SD - Syafril, Syafril (Ibtida'iy : Jurnal Prodi PGMI, 2025)
This study aims to examine the implementation of Project‑Based Learning (PBL) based on the surrounding environment in enhancing elementary school students’ geoscience awareness. The background of this research is grounded in the low conceptual understanding of geoscience and the lack of connection between geography learning and local phenomena at the elementary school level. This research employed a qualitative approach with a case study method. The participants were fifth-grade students at an elementary school in Lombok, Indonesia. Data were collected through participant observation, in-depth interviews, documentation, and field notes. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The results indicate that the application of environment-based PBL effectively improves students’ conceptual understanding of geoscience, environmental awareness, and 21st-century skills. Three dimensions of geoscience awareness were identified: awareness of local phenomena, the relevance of geoscience to daily life, and the importance of maintaining environmental balance. Furthermore, students’ collaboration, communication, and problem-solving skills were strengthened through field exploration project activities. Contextualizing learning by utilizing local potential, such as rivers, cliffs, and types of rocks around the school, enriched the learning experience and strengthened students’ sense of place. These findings contribute to the development of an adaptive and locally relevant PBL-based geography learning model for Indonesian elementary schools. The novelty of this study lies in revealing the process of internalizing students’ geoscience awareness through collaborative exploration of local phenomena. The study recommends strengthening teachers’ roles as facilitators, developing modules based on the surrounding environment, and conducting further studies to broaden the model’s application in various elementary school contexts.